In vitro trypanocidal and cytotoxic activity of essential oils from native plants of the brazilian cerrado (Research, Society and Development, 2020)
Chagas disease (CD) is a major neglected tropical disease that is caused by Trypanosoma cruzi (Chagas, 1909). CD is treated with the antiparasitic drugs nifurtimox and benznidazole, which have several side effects. The market for natural products has grown and the use of plants has emerged as an alternative for the development of novel drugs to cure this disease. In this context, this study reports the chemical analysis of the essential oils from the leaves of Zanthoxylum riedelianum (Rutaceae), Zanthoxylum rhoifolium (Rutaceae) and Kielmeyera coriacea (Calophyllaceae) and the fruits of Xilopia aromática (Annonaceae) and Zanthoxylum rhoifolium (Rutaceae), as well as the trypanocidal and cytotoxic activities of these. The chemical analysis of the oils was performed by gas chromatography coupled to mass spectrometry. The trypanocidal assay was performed on trypomastigote forms of Trypanosoma cruzi, and the evaluation of the cytotoxic activity was performed on the LLCMK2 cell line. The essential oils with stronger trypanocidal activity were those from the leaves of K. coriacea (IC50 = 6.4 µg.mL-1) and fruits of X. aromatica (IC50 = 6.4 µg.mL-1), followed by those from the fruits of Z. rhoifolium (IC50 = 8.1 µg.mL-1). The latter two essentials oils showed a better selectivity index (SI). Additionally, sabinene may be responsible for these properties since it is the major compound present in this essentials oils. The cytotoxic analysis indicated that all of the essential oils evaluated were toxic to the LLCMK2 cells at concentrations higher than 100 µg.mL-1 and therefore they are excellent candidates for the development of novel antiparasitic drugs.